THE INFLUENCE OF LOCAL TAXES, LOCAL LEVIES, AND POPULATION THROUGH LOCAL FINANCIAL INDEPENDENCE ON LOCAL ECONOMIC GROWTH IN KENDAL REGENCY 2014-2024 - Setyawan, Pungki Andreyas; Badjuri, Achmad (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The aim was to determine the effect of regional taxes, levies, and population on regional financial independence. Aimed at indirect regional, levies, and population through economic growth. Methods: This study employed quantitative research. The secondary data used were regional taxes, levies, population, regional financial independence, and economic development. The data source was the 2014-2024 tax reports of the Kendal Regency Statistics Agency (BPS). Data collection used documentation methods. Data analysis used descriptive statistics. Results: The results showed that regional taxes and levies had a significant positive effect. The population had a negative. Regional taxes levied, through financial means, had no significant positive impact. Meanwhile, population, though, had a significant positive effect on economic growth. Keywords: regional taxes, levies, population, regional financial independence, and economic growth